Knowledge Management In Instiki E-Learning To Increase Student Learning Satisfaction - Aniek Suryanti Kusuma; Ketut Agustini; I Gde Wawan Sudatha; I Wayan Sukra Warpala (Telematika, 2022)
Purpose: The use of the concept of knowledge management can manage the knowledge of the teacher or lecturer and then it can be conveyed to the studentsDesign/methodology/approach: Knowledge Management SystemFindings/result: The application of the Knowledge Management System at the INSTIKI LMS was able to increase student learning satisfaction. The results of the questionnaire assessment show that student learning satisfaction increases after implementing INSTIKI e-learning, the average value of studentOriginality/value/state of the art: Implementation of Knowledge Management System on INSTIKI campus